Current Devices in Mitral Valve Replacement and Their Potential Complications - Gheorghe, Livia; Brouwer, Jorn; Wang, Dee Dee; Wunderlich, Nina; Rana, Bushra; Rensing, Benno; Eefting, Frank; Timmers, Leo; Swaans, Martin (Frontiers in Cardiovascular Medicine, 2020)
Mitral regurgitation is one of the most prevalent valvulopathies worldwide, and its surgical treatment is not feasible in all cases. Elderly and frail population, with several comorbidities and left ventricular dysfunction, are often managed conservatively. Percutaneous treatment (repair or replacement) of the mitral valve has emerged as a potential option for those patients with high risk for surgery. Mitral valve repair with the Mitraclip device proved both safety and mortality reduction in patients with severe mitral regurgitation. On the other hand, in the last decade, percutaneous mitral replacement opened new frontiers in the field of cardiac structural interventions. There are few mitral devices, some in the early phase of development, and some waiting for CE Mark approval. The evolution of these devices was more complicated, compared with the aortic technology due to the native mitral valve complexity and access. This review aims to provide an overview of the current devices, their specific features, and potential complications as well.